Acute effect of electroacupuncture at the Zusanli acupoints on decreasing insulin resistance as shown by lowering plasma free fatty acid levels in steroid-background male rats - Lin Jaung-Geng; Cheng Juei-Tang; Ho Wai-Jane; Lee Yu-Chen; Tzeng Chung-Yuh; Lin Rong-Tsung; Chang Shih-Liang (BMC, 2009)
Abstract Background Insulin sensitivity has been enhanced by electroacupuncture (EA) in rats, but the EA phenomenon in an insulin resistant state is still unclear. This study reports the use of a large dose of prednisolone to evaluate the effects of EA in a state of insulin resistance. Methods The plasma levels of free fatty acids (FFAs) were estimated in steroid-background rats (SBRs) and compared with those in healthy rats treated with normal saline. In addition, plasma glucose and endogenous insulin levels were assayed to calculate the homeostasis model assessment (HOMA) index. Intravenous glucose tolerance test (IVGTT) was carried out to compare glucose tolerance. The SBRs were randomly divided into EA-treatment and non-EA treatment groups and 15-Hz EA was applied to the bilateral Zusanli acupoints to investigate its effects on insulin resistance. In addition to an insulin challenge test (ICT) and IVGTT, the plasma levels of FFAs were measured and western blot was performed to help determine the effects of EA on the insulin resistant state. Results The plasma levels of FFAs increased markedly in SBRs, the HOMA index was markedly higher, and glucose tolerance was impaired. EA improved glucose tolerance and insulin sensitivity by decreasing the plasma levels of FFAs. Further, the insulin signaling proteins (IRS1) and glucose transporter isoform protein (GLUT4) in skeletal muscle inhibited by prednisolone recovered after EA. Conclusion Insulin resistance was successfully induced by a large dose of prednisolone in male rats. This insulin resistance can be improved by 15 Hz EA at the bilateral Zusanli acupoints, as shown by decreased plasma levels of FFAs.